The Urgency of Developing School Work Plans in Preparing for Golden Indonesia 2045 - Qomaruddin; Muhammad Shohibuddin; Hamdani; Ali Nurhadi (al-Afkar, Journal For Islamic Studies, 2025)
The School Work Plan is a very urgent activity that needs to be carried out and developed in the world of education as a reference in implementing the educational process, so that the steps that will be taken can be in accordance with the needs of students in the future, especially as the country of Indonesia is expected to become Indonesia. Gold in 2045. Therefore, it is necessary to plan and develop effective school work plans, because without planning and developing work plans that are tailored to the needs of students, educational institutions will be stagnant and even uninterested by the community, therefore, this research focuses in developing school work plans with the hope that they can become a guide in developing school work plans. The results of this research explain that it is urgent to develop school work plans and there is a need to simplify the curriculum so that students focus more on certain subjects. It is hoped that the process of developing this school work plan can produce a generation that is skilled and competent in its field so that it can progress and compete at the international level.